The present situation and prospect of nursing research capacity of clinical nurses in China (临床护士护理科研能力现状及展望) - LI Jianing (李佳凝); WANG Bei (王蓓) (Association of Integrative Nursing, 2022)
The nursing research is most direct factor which stimulates improvement of nursing science and quality of clinical nursing. Given the continuous development of social-economy and scientific technology, nurses should pay more attention on awareness and capacity of scientific research. This paper briefly analyzed the present situation, potential problems and influencing factors of nursing research capacity among clinical nurses in China. Strategies for improving the nursing research capacity were discussed, in order to comprehensively promote the development of discipline of nursing in China. (护理科研是推动护理科学发展最直接的动力, 也是提高临床护理质量的重要手段。随着社会经济的不断发展, 科技水平也在不断提高, 这就要求护理人员不断提高科研意识和科研能力。本文简要分析我国护理科研发展现状, 探讨临床护理科研中存在的问题以及影响临床护士科研能力的因素, 提出改进策略, 旨在更好地促进我国护理科学的全面发展。)